Achieving sustainable development. - PERSAUD, Bishnodat (1994)
Outlines the advantages and drawbacks which size confers on small island developing states. Points out that small islands need support to achieve sustainable development, and to enable them to contribute to global welfare through the special biological resources they control. Suggests the establishment of an international centre for sustainable development of small islands states.